Analisa Pemanfaatan QR Code Terhadap Pengembangan Bahan Ajar Berbasis TPACK dan Moderasi Beragama - Shofia Himayatul Bariroh; Sabarudin (At-Tarbawi: Jurnal Kajian Kependidikan Islam, 2023)
This study aims to analyze TPACK-based teaching materials by using the QR Code as a source of quotations in class. This study uses a type of quantitative research. The results of the study show that utilizing the QR Code as a source of quotations greatly influences students' understanding of the courses they take, especially in religious moderation courses. It can be seen from the calculations using SPSS that all components significantly affect the success of integrating TPACK. That is, the components of TPACK have a large impact on learning. The component that has a significant influence is TCK (0.529) and the one that has less significant influence is the CK component (0.152).